1989
DOI: 10.1088/0953-4075/22/5/006
|View full text |Cite
|
Sign up to set email alerts
|

On the feasibility of detecting parity non-conserving optical rotation at 639 nm in Sm I

Abstract: An experimental study has been made of the nearly degenerate, opposite parity states 4f 66s6p 7G1 and 4f 65d6s 7G1 in samarium to assess the feasibility of using the forbidden M1 transition from the 4f 66s 2 7F0 ground state to the 4f 65d6s 7G1 state for measuring parity non-conserving (PNC) effects. The authors conclude that detection of the PNC optical rotation is not feasible because of the high background rotation present at the M1 wavelength and also because the PNC signal itself would be significantly sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…PNC studies with samarium appear to have no advantages over other systems. Preliminary work showed that PNC optical rotation on the forbidden M1 transition 4f 6 6s 2 7 F 0 − 4f 6 5d6s 7 G 1 , which could have benefited from having close (∼ 10 cm −1 ) opposite parity states, is not feasible [159]. Moreover, it has recently been found, through a term reassignment of several of the odd-parity states in Sm [160], that an estimate of the weak matrix element made in the original proposal for the experiment [161] should be reduced by about 40 times.…”
Section: Ongoing/future Studies Of Pnc In Complex Atomsmentioning
confidence: 99%
“…PNC studies with samarium appear to have no advantages over other systems. Preliminary work showed that PNC optical rotation on the forbidden M1 transition 4f 6 6s 2 7 F 0 − 4f 6 5d6s 7 G 1 , which could have benefited from having close (∼ 10 cm −1 ) opposite parity states, is not feasible [159]. Moreover, it has recently been found, through a term reassignment of several of the odd-parity states in Sm [160], that an estimate of the weak matrix element made in the original proposal for the experiment [161] should be reduced by about 40 times.…”
Section: Ongoing/future Studies Of Pnc In Complex Atomsmentioning
confidence: 99%
“…On the other hand, several groups have investigated the rare earths elements of outershell structure s 2 , similar to Ba, but where the more complex overall configuration gives rise to accidental near-degeneracies between levels of opposite parities. In particular an experimental study has been made of the nearly-degenerate, opposite parity Sm states 4f 6 6s6p 7 G 1 and 4f 6 5d6s 7 G 1 (only 11 cm −1 apart), in order to assess the feasibility of using the forbidden M 1 transition from the 4f 6 6s 2 7 F 0 ground state to the 4f 6 5d6s 7 G 1 state (at 639 nm) for measuring PV effects (Davies et al 1989). Discouragingly several experimental difficulties connected with the application of an electric field in a dense Sm vapour looked insurmountable.…”
Section: Proposals For Experiments Inmentioning
confidence: 99%
“…It also allowed to revise (namely, reduce by a factor of about 40) an estimate of the PNC amplitude in a transition from the ground state of Sm to the 7 G 1 state originally made by the Oxford group [7] (see also Ref. [33] where experimental possibilities of measuring PNC in this transition were investigated). Our revised estimate showed that while the PNC amplitude in this Sm transition is still much larger than in Cs, it is probably somewhat smaller than that in Yb (see above), and no obvious advantages of Sm were found.…”
Section: Spectroscopy and Possible Tests Of Pt-violation In Samariummentioning
confidence: 99%